Experimental behavior of Sporothrix schenckii and Leishmania mexicana in hamsters - González de Polanía, Luz Angela; Alzate, Alberto; Saravia, Nancy (Revista do Instituto de Medicina Tropical de São Paulo, 1990)
The macroscopic description of the pathogenic process of Sporothrix schenckii and Leishmania mexicana spp in hamsters inoculated subcutaneously in the nose provided bases for the differentiation of the behavior of these two microorganisms in a model frequently utilized for their study. Sequential observations over 150 days demonstrated that infections caused by these pathogens results initially in edema and erythema followed by loss of hair, necrosis and ulceration. The pus production was a characteristic presented only by S. schenckii. These clinical signs were observed earlier in sporotrichosis than in L. mexicana infection. Differences in the mean day of appearance were statistically significant. The lesions produced by S. schenckii and L. mexicana in this experimental model share clinical signs, but their incubated period and relative frequency allow us to differentiate them. The circumstances of inoculation such as strain, dose of inoculum, place and route of inoculation are related to the experimental behavior of them.